2017
DOI: 10.1175/jas-d-16-0104.1
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Gravity Wave Parameterization in the Whole Atmosphere Community Climate Model: Motivation and Results

Abstract: The current standard version of the Whole Atmosphere Community Climate Model (WACCM) simulates Southern Hemisphere winter and spring temperatures that are too cold compared with observations. This “cold-pole bias” leads to unrealistically low ozone column amounts in Antarctic spring. Here, the cold-pole problem is addressed by introducing additional mechanical forcing of the circulation via parameterized gravity waves. Insofar as observational guidance is ambiguous regarding the gravity waves that might be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
296
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(307 citation statements)
references
References 46 publications
9
296
2
Order By: Relevance
“…This new development allows for the examination of the effects of SO 2 injections on the QBO, which are presented in Richter et al (), motivated in part by previous work that has suggested that stratospheric sulfate geoengineering could severely alter the QBO (Aquila et al, ). Additional tuning of the gravity wave parameterization in WACCM has significantly reduced the bias of the temperatures in the Antarctic polar vortex, which is critical to calculating ozone loss (Garcia et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This new development allows for the examination of the effects of SO 2 injections on the QBO, which are presented in Richter et al (), motivated in part by previous work that has suggested that stratospheric sulfate geoengineering could severely alter the QBO (Aquila et al, ). Additional tuning of the gravity wave parameterization in WACCM has significantly reduced the bias of the temperatures in the Antarctic polar vortex, which is critical to calculating ozone loss (Garcia et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, except for orography, even the coupling to physical GW source processes is missing in many models. Initial parameters of the GW parametrization schemes have to be chosen and the mean wind and temperature fields produced by the GCM are highly sensitive to this parameter choice at all altitudes (e.g., Sigmond and Scinocca, 2010;Garcia et al, 2017;Medvedev and Klaassen, 2000;Yigit et al, 2008). The T/I is a region where GWs are one of the main driving forces and sensitivity to uncertainties in the GW parametrizations is high.…”
Section: Q T Trinh Et Al: Satellite Observations Of Vertical Couplmentioning
confidence: 99%
“…[] and Garcia et al . [] discuss in detail the sensitivity of these results to uncertainties in orographic gravity wave parameterizations.…”
Section: Data Sets and Model Simulationsmentioning
confidence: 99%